Application of Modified Chitosan for Recovery of Heavy Metals Found in Spent Batteries - Babakhani, Ataollah (Université d'Ottawa / University of Ottawa, 2022)
Finding economical and environmentally friendly processes to recover heavy metals (HMs) from spent batteries is a research priority to move toward sustainability. Adsorption seems an acceptable procedure to replace the current separation/purification stage of hydrometallurgical techniques. Chitosan is an efficient adsorbent for HM uptake from aqueous solutions. Nevertheless, in practice, chitosan modification is unavoidable to improve its physicochemical properties. Sodium tripolyphosphate is an environmentally benign crosslinker that can be used for chitosan modification. In addition, ion-imprinting technique could potentially enhance the adsorption efficiency and selectivity of crosslinked chitosan. Considering the above, the primary purposes of this research were: investigating the adsorption efficiency of chitosan for heavy metals uptake from synthetic solutions; modifying chitosan by crosslinking alone and combined with ion-imprinting techniques to improve the physicochemical properties as well as adsorption capacity and selectivity of chitosan; evaluating and comparing the adsorption efficiency of modified chitosan beads for the adsorption of Cd(II), Ni(II) and Co(II) in single and multicomponent batch adsorption systems. Chitosan and sodium tripolyphosphate crosslinked chitosan beads were prepared to remove Cd(II) from aqueous solution in the first phase. FTIR and XRD of the synthesized beads showed partial consumption of chitosan amine groups and a decrease in crystallinity of chitosan structure over crosslinking reaction. The isotherm and thermodynamic studies showed that Langmuir isotherm was the best fit to the experimental data of Cd(II) adsorption on crosslinked chitosan and all the adsorption reactions were endothermic and spontaneous. A reduced quadratic model, constructed by the Response Surface Methodology (RSM), indicated that the Cd(II) adsorption uptake of 99.87 (mg/g) was achieved at 55 °C and 2.92 % (w/v) crosslinking degree. Then, chitosan and crosslinked chitosan beads by sodium tripolyphosphate were used for Ni(II) adsorption from aqueous media in the second phase. The BET characterization showed that increasing the crosslinking degree reduced the chitosan beads' surface area and their total pore volume. The Langmuir model described the experimental results best and showed that the maximum adsorption capacity of chitosan (80.00 mg/g) decreased after crosslinking (52.36 mg/g). In addition, a reduced quadratic model with a correlation coefficient of 0.96 was established to correlate the adsorption uptake of Ni(II) with pH and crosslinking degree. In the third phase, the adsorption of Ni(II) and Cd(II) ions from single and binary metal ions solutions onto chitosan and crosslinked chitosan beads was studied. The extended Freundlich model fitted the adsorption equilibrium data in the binary system, implying the existence of preference in the order of Ni(II) > Cd(II). Desorption studies with a mixture of NaCl and H2SO4 were also conducted during this phase, demonstrating a desorption efficiency of greater than 85 %. In the fourth phase, the removal of cadmium from aqueous solution was examined using a novel Cd(II)-imprinted crosslinked chitosan. SEM, FTIR, TGA, and BET characterizations revealed that the ion-imprinted chitosan beads had better physicochemical properties than chitosan beads and superior potential adsorption properties than non-imprinted crosslinked chitosan beads. The isotherm and thermodynamic studies revealed that the Langmuir isotherm fitted the Cd(II) experimental data the best, and the adsorption reactions were spontaneous and endothermic. The kinetics data were also best fitted by the pseudo-second-order equation. Finally, the ion-imprinted crosslinked chitosan beads were employed for the selective adsorption of Cd(II) in a competitive adsorption system of Cd(II)-Ni(II)-Co(II) in phase five. The characterization of the prepared adsorbents was performed using XRD and BET, showing a higher surface area of ion-imprinted crosslinked chitosan than non-imprinted crosslinked chitosan beads. The Extended Langmuir model fitted the experimental results obtained from the multi-component system, indicating that ion-imprinted crosslinked chitosan had a higher total metal uptake with better selectivity toward Cd(II) uptake compared to non-imprinted crosslinked chitosan. Studying the adsorption mechanism in a ternary system showed that the adsorption was governed by chemical binding and ion exchange mechanisms in the ternary system. In conclusion, crosslinking by sodium tripolyphosphate improved chitosan physiochemical properties; however, it resulted in a decrease in HM adsorption uptake. The RSM was used to assess the effect of pH, temperature, and crosslinking degree and optimize the adsorption uptake of chitosan. Also, ion-imprinting was effective in enhancing the adsorption capacity and selectivity of crosslinked chitosan for the ion used as a template (Cd(II)) in preparing ion-imprinted crosslinked chitosan.
Keywords: Ni(II); Cd(II); Co(II); Heavy metals; Batch adsorption; Competitive adsorption; Chitosan; Adsorption mechanism; Isotherm study; Kinetics study; Thermodynamic study; Characterization; Statistical analysis; Selectivity; Crosslinking; Ion-imprinting; Chitosan modification